2005
DOI: 10.1636/04-96.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cannibalism Among Newly Hatched Wolf Spiders (Lycosidae, Pardosa Amentata)

Abstract: Cannibalism is a common phenomenon among young wolf spiders (Lycosidae). The purpose of this study was to investigate how various factors influence cannibalistic tendencies in hatchlings of Pardosa amentata (Clerk 1757). The basic experimental approach was to place pairs of unfed hatchlings of similar body mass in small containers without prey and to measure if and when cannibalism happened. From the data, we identified three different cannibalistic strategies. One large group of hatchlings never cannibalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…For instance, Pfennig et al (1993) observed direct siblicide and cannibalism in their study on polyphenism in tadpoles of the spadfoot toad (Scaphiopus bombifrons), and they found that carnivores consume significantly fewer siblings than nonsiblings. A majority of studies report indirect evidence for cannibalism by observing that individuals disappeared and remaining bodies or body parts (dragonfly larvae Aeshna juncea and Tramea carolina [Van Buskirk 1989; damselfly larvae Megaloprepus coerulatus [Fincke 1994]; wolf spiders Pardosa amentata [Hvam et al 2005]), not allowing the discrimination between nest-mate killing and cannibalism and the associated fitness consequences. With the simulation of the survival of victims and survivors in control individuals, that is, noninteracting ''pairs,'' we created the distribution of expected survival probabilities for victims and survivors under the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Pfennig et al (1993) observed direct siblicide and cannibalism in their study on polyphenism in tadpoles of the spadfoot toad (Scaphiopus bombifrons), and they found that carnivores consume significantly fewer siblings than nonsiblings. A majority of studies report indirect evidence for cannibalism by observing that individuals disappeared and remaining bodies or body parts (dragonfly larvae Aeshna juncea and Tramea carolina [Van Buskirk 1989; damselfly larvae Megaloprepus coerulatus [Fincke 1994]; wolf spiders Pardosa amentata [Hvam et al 2005]), not allowing the discrimination between nest-mate killing and cannibalism and the associated fitness consequences. With the simulation of the survival of victims and survivors in control individuals, that is, noninteracting ''pairs,'' we created the distribution of expected survival probabilities for victims and survivors under the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Conspecific killing, siblicide, and cannibalism are common behaviors for invertebrates (e.g., Fincke 1994;Bilde and Lubin 2001;Hvam et al 2005) and these behaviors occur also in vertebrates (e.g., O'Connor 1978;Pfennig 1997). However, clear experimental separation for killing and siblicide and their fitness consequences (i.e., whether cannibalized individuals got killed or whether they died for another reason) is still scarce, probably partly due to the difficulty of observing the killing events per se.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannibalism, the ingestion of all or part of a conspecific (Pfennig 1997), occurs naturally in a wide range of animals (Pfennig 1997;Osawa 2002;Hvam et al 2005). However, its impact within populations typically has elicited only limited attention (Fox 1975;Polis 1981;Elgar & Crespi 1992), and it remains relatively poorly understood (Wilder & Rypstra 2010.…”
mentioning
confidence: 99%